2014
DOI: 10.1016/j.jinsphys.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses from the wind-sensitive interneuron population in four cockroach species

Abstract: The wind-sensitive insect cercal sensory system is involved in important behaviors including predator detection and initiating terrestrial escape responses as well as flight maintenance. However, not all insects possessing a cercal system exhibit these behaviors. In cockroaches, wind evokes strong terrestrial escape responses in Periplaneta americana and Blattella germanica, but only weak escape responses in Blaberus craniifer and no escape responses in Gromphadorhina portentosa. Both P. americana and Blab. cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…We quantified the filiform afferent response by rectifying and integrating the signal averaged neural response elicited by different wind velocities (See Methods for more detail). McGorry et al (2014) found that the WSI responses in these same three species were not consistent throughout the 250 ms duration of the wind stimulus. Compared to the Second 150 ms of the response, the First 100 ms of the response: 1) contained more overall spikes; 2) contained more large amplitude spikes; and 3) had a faster spiking rate for the WSI population (Fig.…”
Section: 0 Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…We quantified the filiform afferent response by rectifying and integrating the signal averaged neural response elicited by different wind velocities (See Methods for more detail). McGorry et al (2014) found that the WSI responses in these same three species were not consistent throughout the 250 ms duration of the wind stimulus. Compared to the Second 150 ms of the response, the First 100 ms of the response: 1) contained more overall spikes; 2) contained more large amplitude spikes; and 3) had a faster spiking rate for the WSI population (Fig.…”
Section: 0 Resultsmentioning
confidence: 97%
“…Therefore, the First 100 ms and Second 150 ms of the responses were analyzed separately. To directly relate the filiform afferent responses to the WSI responses from McGorry et al (2014), we analyzed the filiform afferent responses in the same manner by analyzing the responses during the First 100 ms and Second 150 ms of the stimulus separately.…”
Section: 0 Resultsmentioning
confidence: 99%
See 3 more Smart Citations